PROSES BERTEMUNYA KEPENTINGAN EKONOMI DAN POLITIK DIBALIK KONFLIK ETNIS KALIMANTAN TENGAH - Fawaidi, Ach; Erawan, I Ketut Putra; Bandiyah, Bandiyah (Jurnal Nawala Politika; 2021: Jurnal Ilmu Politik 2021, 2020)
ABSTRACT                                                                                This study explains the conflict ethnic Dayak and Madura in Sampit, Central Kalimantan. The problem discussed is how the meeting of economic and political factors caused a conflict and become one movement against Madura. This research was an explanatory research using qualitative methods. This research used collective action theory and the mobilization structure concept. The results of this research indicated the meeting process occurred when the Dayak political elite was not included in the echelons position I, II, and III in the Regional Government East Kotawaringin which will be inaugurated on February 2001. Those who refuse the inauguration, took advantage of anti-Madura sentiments due to economic disparity. The sentiment was used to mobilize the Dayak into one movement directed into riots. In the meeting process of them showed that there was a link between economic factors and political competition in Sampit.   Keywords : Economic Interest, Political Interest, Sampit Conflict